LEARNING METHODS: THE IMPLEMENTATION OF LECTURE METHOD IN LEARNING FIQIH AT TUBAN ISLAMIC PRIMARY SCHOOL - Novita, Nina; Agustin, Nurhaningtyas; Pradana, Akhmad Aji; Mubaidilla, Irfa'i Alfian (International Conference on Humanity Education and Society (ICHES), 2024)
Learning is a process that requires a dialogical relationship between educators and students. In delivering learning materials, appropriate methods are needed to transfer knowledge from teacher to students. Learning methods can be interpreted as the methods used to implement plans that have been prepared on the practical activities to achieve learning objectives. Choosing a learning method that suits the characteristics of students can make it easier for educators to deliver the learning materials. The lecture method is a classical method that is frequently used in various learning. This method uses verbal explanations carried out by educators directly in front of students at the front of the class. This research, which uses the qualitative case study design, aims to determine the implementation of the lecture method in 3rd class students on learning fiqh at Tuban Islamic Elementary School.